Effect Of Natural And Anthropogenic Factors On The Formation Of The Quality Of Plant Products - NekosА. N.; Semibratova, P. V.; VysotskaЕ. V.; PorvanА. Р.; PetukhovaА. L. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2014)
We consider the degree of influence of natural and anthropogenic factors on the content of trace elements in foods of plant origin, using the methods of analysis of variance. The laws of accumulation of trace elements in plant products, depending on soil biodiversity, natural area, as well as the level of pollution of surface waters.